2023
DOI: 10.1007/s11356-023-27767-8
|View full text |Cite
|
Sign up to set email alerts
|

Algal sorbents and prospects for their application in the sustainable recovery of rare earth elements from E-waste

Abstract: Efficient and sustainable secondary sourcing of Rare-Earth Elements (REE) is essential to counter supply bottlenecks and the impacts associated with primary mining. Recycled electronic waste (E-waste) is considered a promising REE source and hydrometallurgical methods followed by chemical separation techniques (usually solvent extraction) have been successfully applied to these wastes with high REE yields. However, the generation of acidic and organic waste streams is considered unsustainable and has led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…Despite these advantages, certain pyrometallurgical processes still necessitate chemical inputs and result in waste generation. While pyrometallurgical recycling enables scalability and involves fewer chemicals (flame retardants, furans, and phenolics) [16]), it does release harmful gases like dioxins, carbon dioxide, and volatile metals such as mercury [91]. Cui and Zhang demonstrated that polychlorinated biphenyls (PCBs) can generate a mixed oxide, primarily containing lead (Pb) and zinc (Zn), as slag through a top-blown reactor.…”
Section: Pyrometallurgical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these advantages, certain pyrometallurgical processes still necessitate chemical inputs and result in waste generation. While pyrometallurgical recycling enables scalability and involves fewer chemicals (flame retardants, furans, and phenolics) [16]), it does release harmful gases like dioxins, carbon dioxide, and volatile metals such as mercury [91]. Cui and Zhang demonstrated that polychlorinated biphenyls (PCBs) can generate a mixed oxide, primarily containing lead (Pb) and zinc (Zn), as slag through a top-blown reactor.…”
Section: Pyrometallurgical Methodsmentioning
confidence: 99%
“…Various purification processes can be employed to recover precious metals present in the leachates. Solvent extraction, chemical precipitation, ion exchange, adsorption, electrochemical deposition, and more innovative eutectic freeze crystallization are among the most common separation methods [91,98]. Although precipitation and ionic liquid methods are highly efficient for metal recovery, the use of precipitation often results in the generation of secondary sludge, which can lead to pollution [40].…”
Section: Approaches For Separation Of Reesmentioning
confidence: 99%
See 2 more Smart Citations
“…Solvent extraction, or liquid-liquid extraction is highly used and is commercially exploited to produce high purity single REEs; however, it is an inefficient, labour-intensive and time-consuming method (Opare et al, 2021). Adsorption of REEs can also be carried out with either organic or inorganic compounds, depending on the element considered; the effectiveness of this method is strongly related to contact time, adsorbent dose, initial concentration, solution pH and temperature (Anastopoulos et al, 2016;Iannicelli-Zubiani et al, 2015;Pinto et al, 2023). Ion exchange is another widely exploited method that is generally carried out exploiting different resins (Chen et al, 2017;Hérès et al, 2018) and MOFs.…”
Section: Introductionmentioning
confidence: 99%